PEGARUH KONFLIK PERAN DAN KETIDAKJELASAN PERAN TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERATING (Studi Empiris pada Kantor Akuntan Publik di Pekanbaru, Padang dan Medan - Ilman, Rizki; Kirmizi, Kirmizi; Natariasari, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to examine the influence of role conflict and role ambiguity to auditor performance. This research also examined whether the emotional quotient is able to moderate the influence of role conflict and role ambiguity to Auditor performance. The population in this research is the auditor who worked on Public Accounting Firm in Pekanbaru, Padang, and Medan. The total sample in this research were 25 Public Accountant Firm with 100 respondents. The sampling technique in this research using purposive sampling method with the criteria of all auditors (partner, manager, senior auditor and junior auditor) who works in the Public Accountant Firm with experience working as an auditor at least 1 year. These results indicate that 1) Role Conflict have significant influence to auditor Performance with significantly value 0,000. 2) Role Ambiguity have significant influence to Auditor performance with a significantly value of 0.024. 3) Emotional quotient is able to moderate influence Role Conflict to Auditor Performance with significantly value 0,000. 4) Emotional quotient is able to moderate influence Role ambiguity to Auditor performance with significanly value 0,035.Keyword : Auditor Performance, Role Conflict, Role Ambiguity, Emotional Quotient